A Framework for a Pro-Growth, Pro-Poor Transport Strategy : Guidance Note - Mitiku, Tesfamichael Nahusenay (World Bank, Washington, DC, 2014)
A pro-growth, pro-poor transport strategy (PGPTS) responsive to the second generation poverty reduction strategies (SGPRSs) and the millennium development goals (MDGs) are essential instruments to promote transport development that facilitates economic growth and poverty reduction. However, the national poverty reduction and transport strategy reviews, undertaken by Sub-Saharan Africa Transport Policy Program (SSATP) member countries, and the MDG review, have shown that the existing transport strategies are deficient in many respects in supporting this objective. The strategies have not been successful in delivering adequate access to the rural and urban poor in Africa to reach economic opportunities, and to social and administrative services. The purpose of this framework document (guidance note) is to highlight possible options for the development of a PGPTS. It identifies the questions that need to be asked and the choices that need to be made in framing such a strategy. It offers, at each stage, a checklist of issues for consideration and some examples of good practices. Its aim is to encourage policy-makers and planners to adopt a structured approach to assessing gaps, defining sectoral vision and goals, and mapping transport interventions and policy changes required to anchor transport in growth and poverty reduction. This guidance note is based on development scenarios and strategy formulation processes in Sub-Saharan Africa countries, and it is designed to facilitate the development of transport strategies that will support the achievement of the MDGs in these countries, and increase Africa's trade competitiveness and integration.